The Strategic Role of Digital Marketing and Tourist Experience in Indonesia’s Tourism Competitiveness - Ratih Nur Setyaningsih (Jurnal Dinamika Administrasi Bisnis, 2026)
Indonesia’s tourism sector is undergoing significant transformation driven by digital disruption and the growing shift toward experience-oriented travel. This study aims to examine the strategic role of digital marketing and tourist experience in enhancing tourism competitiveness in Indonesia. An integrative literature review approach is employed to synthesize findings from relevant peer-reviewed studies published between 2020 and 2024. The analysis is conducted through thematic synthesis to identify key patterns and relationships among digital marketing strategies, experiential value, and tourism performance. The findings indicate that digital marketing, particularly through social media marketing, electronic word-of-mouth (e-WOM), and user-generated content (UGC), plays a significant role in shaping destination image, enhancing tourist engagement, and influencing travel decision-making. In parallel, tourist experience—especially memorable and immersive experiences—emerges as a critical determinant of satisfaction, loyalty, and revisit intention. The integration of advanced technologies and human-centric approaches under the Marketing 5.0 paradigm further strengthens value creation by enabling personalized and data-driven tourism marketing strategies. In addition, integrated marketing communication (IMC) and event-based tourism are identified as strategic mechanisms that ensure message consistency and reinforce destination branding. Based on the synthesis, this study proposes an integrative conceptual framework that connects technological (digital marketing and Marketing 5.0), experiential (memorable tourism experience), and strategic communication (IMC) dimensions in explaining tourism competitiveness. The findings contribute to the advancement of tourism marketing literature and provide practical implications for policymakers, destination managers, and industry practitioners in developing more competitive and sustainable tourism strategies in Indonesia.